QRB (quick-response book) - Mohd Noh, Siti Nurhanim; Sulaiman, Nur Aisyah; Mahmood, Mahadi (Universiti Teknologi MARA, Kedah, 2017)
The QRB is design to ease the process of gaining a book's information with minimum effort. It will assist the library user to retrieve information such as title, call number, author, shelves and also abstract of the book. It also will minimize time and avoid the library user to open and read the book one by one from one shelve to another shelve. The user will gain bibliographic details of the book with abstract by scanning the QR code placed on the book spine. Fast and easy to retrieve bibliographic details and also book abstract. Users only scan the QR code and save to their mobile phone. All the details can be read anywhere and any place within their free time.